Four new species of the genus Phryganogryllacris (Orthoptera, Gryllacrididae, Gryllacridinae) in China - Li, Miaomiao; Liu, Xianwei; Li, Kai (Zootaxa, 2016)
A taxonomic study of the genus Phryganogryllacris Karny, 1937 is presented. Four new species are described: Phryganogryllacris brevipennis sp. nov., Phryganogryllacris hubeiensis sp. nov., Phryganogryllacris sigillata sp. nov., Phryganogryllacris fanjingshanensis sp. nov.. A key to the species and the distributional data of Phryganogryllacris are provided.